Treatment of recurrent aphthous stomatitis by laser therapy: A systematic review of the literature - Pavlić, Verica; Vujić-Aleksić, Vesna; Aoki, Akira; Nežić, Lana (Vojnosanitetski pregled, 2015)
Background/Aim. Recurrent aphthous stomatitis (RAS) is defined as multifactor immunologic inflammatory lesions in the oral cavity, characterized by painful, recurrent single/multiple, shallow, round or ovoid ulcerations of mucosal tissues. To date, a considerable number of RAS treatment protocols have been suggested, but since the etiology of RAS is idiopathic, these treatment options have symptomatic rather than curative or preventive effect. Recently, it has been suggested that laser therapy could be successfully used as an efficient treatment approach in therapy of RAS. Therefore, the aim of this review was to estimate the effects of laser therapy in treatment of RAS analyzing results of clinical studies published in peer reviewed journals. Methods. The studies published until 31 December 2013 were obtained from the Medline/PubMed, Science Direct and Cochrane Library of the Cochrane Collaboration (CENTRAL) online databases, using following search terms and key words: “laser” AND “recurrent aphthous stomatitis”, “laser” AND “aphthous”, and “laser” AND “aphthae”. In total 4 original research articles met the all required inclusion/exclusion criteria, and were used for this review. The main outcome measures assessed were: a reduction of pain associated with RAS and a reduction in episode duration (faster RAS healing). Results. The assessed literature demonstrates the benefits of laser therapy mainly due to immediate analgesia and ability to speed up a RAS healing process. Conclusion. Even though the assessed literature suggests beneficial outcomes of laser therapy in treatment of RAS, these results should be interpreted with caution. The issues related to the study designs and different sets of laser irradiation parameters of a limited number of available studies with the same treatment outcomes prevent us from making definite conclusions
Keywords: laser therapy; low level; stomatitis aphthous; recurrence; treatment outcome